Aplikasi Kinemaster sebagai Media Pembelajaran Daring pada Mata Pelajaran Pendidikan Agama Islam - Kurnia Mulyani, Dessy (Ar-Rusyd: Jurnal Pendidikan Agama Islam, 2022)
This research is motivated by the importance of using digital media as online learning media in the industrial era 4.0. The purpose of this study is to describe the process of developing videos using the kinemaster application as an online learning medium for Islamic religious education subjects, so as to increase creativity and innovation for educators in developing online learning media. The Kinemaster application is software on a smartphone that can be a solution in the development of today's online learning media. This study uses research and development methods using the ADDIE instructional model, the development model has five stages, namely (a) analysis, (b) design, (c) development, ( d) implementation, (e) evaluation. However, this research is still in the ADD stage, namely analysis, design and development. This study describes the video editing process using the kinemaster application as an online learning medium. The results of the pilot study were limited to 20 students of Class VI SD with a percentage of 85% which was considered very good. The final results can show that 1) the use of the kinemaster application in Islamic Religious Education subjects is appropriate for use in the online learning process; 2) creative and innovative video shows are able to increase students' understanding of learning so that it is more interesting and not boring; 3) online learning carried out using video viewing makes learning more practical.